Hubungan Pengetahuan tentang Scabies dengan Kejadian Scabies pada Remaja Santri di Pondok Pesantren Darussalam Desa Gebugan Kecamatan Bergas Kabupaten Semarang - M Nur Dhuha; setyoningrum, umi (Indonesian Journal of Nursing Research (IJNR), 2023)
Scabies is a skin disease that is often found in dense residential areas such as Islamic boarding schools. If this disease is not cured, it will disturb the rest and comfort of the students, which in turn hinders the achievement of learning outcomes. One of the factors that influence the incidence of scabies is the knowledge of students regarding the disease. This research to determine the relationship between knowledge and the incidence of scabies in adolescent students at the Darussalam Islamic Boarding School, Bergas , Semarang Regency. Design research is descriptive correlative with a cross sectional approach. The population of this research is students at the Darussalam Islamic Boarding School,  Bergas District, Semarang Regency with a sample of 78 people taken by random sampling technique. The data collection tool used was a questionnaire and the data were analyzed by using the chi square test which was processed by the SPSS data processing program. Most of the students who had knowledge about scabies were in the sufficient category, as many as 53 of 78 respondents (67.9%). Most students were not scabies, as many as 54 of 78 respondents (69.2%). There is a relationship of knowledge with the incidence of scabies in adolescent students at the Darussalam Islamic Boarding School, Bergas District, Semarang Regency, obtained p value of 0.001 < (0.05). It is better for students to improve their knowledge and personal hygiene and the Islamic boarding school should carry out periodic mass treatment and health education on an ongoing basis.   Abstrak Scabies merupakan penyakit kulit yang banyak ditemukan di lingkungan padat hunian seperti pondok pesantren. Penyakit ini jika tidak disembuhkna menganggu istirahat dan kenyamanan santri yang pada akhirnya menghambat pencapaian hasil belajar. Salah satu faktor yang mempengaruhi kejadian scabies adalah pengetahuan santri terkait penyakit tersebut. Tujuan penelitian ini untuk mengetahui hubungan pengetahuan tentang scabies dengan kejadian scabies pada remaja santri di Pondok Pesantren Darussalam Desa Gebugan Kecamatan Bergas Kabupaten Semarang.  Desain penelitian ini deskriptif korelatif dengan pendekatan cross sectional. Populasi penelitian ini remaja Pondok Pesantren Darussalam Bergas Kabupaten Semarang dengan sampel 78 orang. Teknik random sampling. Alat pengumpulan data yang digunakan adalah kuesioner dan data dianalisis dengan uji chi square yang diolah dengan program pengolahan data SPSS. Remaja santri sebagian besar mempunyai pengetahuan tentang scabies kategori cukup yaitu sebanyak  53 dari 78 responden (67,9%). Remaja sebagian besar  tidak scabies yaitu sebanyak  54 dari 78 responden (69,2%). Ada hubungan pengetahuan tentang scabies dengan kejadian scabies pada remaja Pondok Pesantren Darussalam Bergas Kabupaten Semarang, didapatkan  p value sebesar 0,001 < α (0,05). Pengetahuan dan personal hygiene remaja pondok pesantren sebaiknya ditingkatkan dengan melakukan pengobatan masal berkala dan penyuluhan kesehatan secara berkesinambungan.